Context-Tailored Food-Based Nutrition Education and Counseling for Pregnant Women to Improve Birth Outcomes: A Cluster-Randomized Controlled Trial in Rural Malawi - Kamudoni, Penjani Rhoda (2024)
BackgroundInadequate maternal dietary intakes remain a public health challenge in low-income countries like Malawi and can cause adverse birth outcomes. ObjectivesTo improve maternal dietary intakes and thus reduce the prevalence of adverse birth outcomes in rural Malawi. MethodsWe performed a 2-armed (1:1) cluster-randomized controlled trial in Southern Malawi, enrolling pregnant women at gestational age 12–18 wk. Twenty villages (clusters) were randomly assigned to an intervention or a control group. A nutrition education and counseling (NEC) intervention consisted of education sessions followed by cooking demonstrations and counseling sessions. The women were encouraged to use locally available nutrient-dense foods to enhance dietary adequacy and -diversity. We applied linear programming to identify food combinations that could increase micronutrient intakes. The control group received standard antenatal health education. ResultsAmong the 311 women recruited, 187 (60%) completed the trial. We found no significant difference in mean birth weights recorded within 1 or 24 h of birth between the intervention and control groups. Intervention infants had greater birth length (P = 0.043) and abdominal circumference (P = 0.007) compared to controls, whereas other birth outcomes did not differ significantly. Notably, a quantile analysis revealed that the NEC intervention favored birth weight among mothers with a height below the mean height of the participant sample (156 cm) (P-interaction = 0.043). ConclusionsTailoring NEC in food-insecure communities did not result in a significant difference in birth weight among infants of the participating mothers, but mean birth length and abdominal circumference were greater in the intervention group compared to controls. We noted that the NEC intervention favored birth weight among mothers with a lower height than the mean sample height. Our results warrant further investigation into offering tailored NEC early in pregnancy and on a larger scale.This trial was registered at clinicaltrials.gov as NCT03136393.